Search for CP violation in tt¯ production and decay in proton-proton collisions at √s=8 TeV - Khachatryan, Vardan; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2017)
: The results of a first search for CP violation in the production and decay of top quark-antiquark (tt¯) pairs are presented. The search is based on asymmetries in T-odd, triple-product correlation observables, where T is the time-reversal operator. The analysis uses a sample of proton-proton collisions at √ s = 8 TeV collected by the CMS experiment, corresponding to an integrated luminosity of 19.7 fb−1 . Events are selected having one electron or muon and at least four jets. The T-odd observables are measured using four-momentum vectors associated with tt¯ production and decay. The measured asymmetries exhibit no evidence for CP-violating effects, consistent with the expectation from the standard model.